Letter (copy) : Developments in Spain - Citrine, Walter, 1887-1983
012b-0023-001 Secretary's. WMC/FC/EK/1377. 27th July, 1939. Senor J. I. de Lizaso, Basque Delegation, 14, Eccleston Square, London, S.W.1. Dear Senor Lizaso, DEVELOPMENTS IN SPAIN. Many thanks for your letter of the 26th instant enclosing further information regarding developments in Spain. I am very glad to have this. With kind regards Yours sincerely, General Secretary 292/946/12b/23